Nurses in the labor market: professional insertion, competencies and skills - Vilanice Alves de Araújo Püschel; Dafeni Costa; Priscila Patrício Reis; Larissa Bertacchini de Oliveira; Fábio da Costa Carbogim
ABSTRACT Objective: to characterize nurses graduated from the School of Nursing of the University of São Paulo, from 2006 to 2012; verify their entry, facilitating factors and difficulties of these graduates in the labor market and to consider their skills and competences in the world of work. Method: an exploratory, descriptive study with a qualitative approach. Results: out of 505 graduates, 172 (34.1%) participated in the research. Entry into the labor market was mainly via public hospital institutions, in the SE of Brazil, in the caregiving sectors. The greater part remained from one to two years in their first job. Most agreed that they were prepared to meet the health needs of the population. Furthermore, they had been encouraged to seek systematic and continuous improvement in a critical, reflexive and creative way, while combining technical-scientific knowledge and personal skills. Conclusion: the results show that the University of São Paulo has been preparing nurses for work in the labor market, in accordance with the provisions of the National Curricular Guidelines.